Logika Induktif dan Deduktif Dalam Tradisi Pemikiran USUL AL-FIQH - A. Yasid, A. Yasid (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Logic occupies a central position in the tradition of usul al-fiqh thought. Besides referring to the verbal revelation, the formulation of the rules of usul al-fiqh is also based on formal logic so that it cannot be easily cracked all along. The logic with its main attention on the activity of the preparation of the ri ght argument is built to study the various methods and principles used to distinguish the reasoning straight and distorted one. Inductive and deductive logic are typical ways of working in a world of usul al-fiqh thought. Inductive logic is used to draw conclusions from individual cases that have a range of very specific to general conclusions. Whereas deductive logic is the opposite way. It?s used to draw conclusions from things that are common to the individual case. In the tradition of usul al-fiqh thinking, inductive logic is often used by Ahnaf schools. While many of deductive logics are demonstrated by the yurisprudence of Mutakallimin followed by the majority of Islamic Juries.